Efektivitas Terapi Spiritual Relaksasi Benson terhadap Kecemasan Ibu Pre Sectio Caesarea (Window of Nursing Journal, 2025)
Pre-operative anxiety in patients is a psychological response associated with excessive worry perceived by the patient as a threat when undergoing surgical procedures. This study aims to determine the effect of Benson's relaxation spiritual therapy on the anxiety of mothers before Cesarean section at RSIA Sitti Khadijah 1 Muhammadiyah Branch, Makassar. The research design used in this study is a Quasi Experiment design with a Non-Equivalent control group Pretest and Posttest method. Sampling was determined using Purposive Sampling based on inclusion and exclusion criteria with a sample size of 58 respondents. The statistical test used was the paired sample T test with a significance α < 0.005. The results of anxiety before the provision of Benson's relaxation therapy showed mild anxiety in 30%, moderate in 61.9%, and severe in 6.9%. After the provision of Benson's relaxation therapy, anxiety levels changed to moderate in 20.6%, mild in 68.8%, and no anxiety in 10.3% in mothers preSC. The research results show that there is an effect of Benson's spiritual relaxation therapy on anxiety in mothers preCesarean Section, with the statistical analysis using the paired T-test at a 95% confidence level showing a value of ρ= 0.000 < 0.005. The conclusion of this study is that Benson's spiritual relaxation therapy has an effect on anxiety in mothers preCesarean Section at RSIA Sitti Khadijah 1 Muhammadiyah Branch Makassar. The recommendation is for nurses and other healthcare providers to implement Benson's spiritual relaxation therapy as part of the non-pharmacological management in addressing anxiety in patients undergoing pre-operative Cesarean Section.